2019
DOI: 10.1007/s10877-019-00318-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different PEEP levels on electrical impedance tomography findings in patients under general anesthesia ventilated in the lateral decubitus position

Abstract: To determine the effect of various PEEP levels on electrical impedance tomography (EIT) measured differences in regional ventilation, hemodynamics, lung mechanics and parameters of alveolar gas exchange. Thirty three patients scheduled for elective urologic surgery in general anesthesia in lateral decubitus position were randomized into three groups-PEEP 0, 5 and 10 mbar. EIT recording, arterial blood gas analysis and hemodynamic parameters were captured at three timepointsbefore induction (T0), 5 min after la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
2
6
0
1
Order By: Relevance
“…Moreover, analysis of ventilation proportion of left and right lung indicated significant difference after intubation until to the end of surgery. This finding corresponds with previous studies which showed a significant shift of ventilation towards the nondependent lung after being positioned on their side (7). In left lateral position, the ventilation gradient is redistributed along the gravitational axis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, analysis of ventilation proportion of left and right lung indicated significant difference after intubation until to the end of surgery. This finding corresponds with previous studies which showed a significant shift of ventilation towards the nondependent lung after being positioned on their side (7). In left lateral position, the ventilation gradient is redistributed along the gravitational axis.…”
Section: Discussionsupporting
confidence: 92%
“…This is the known gravity-dependent phenomena that dependent lung regions receive a higher portion of inspired gas in lateral position during spontaneous tidal breathing. However, after induction of general anesthesia, lateral positioning has shown to cause curvature of the diaphragm by abdominal content and basal parts of the dependent lung may become atelectatic (7). In addition, the lung compliance is decreased and a distinct redistribution of ventilation in favor of the dependent regions is also happened when in lateral decubitus position (8).…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of GREIT is to optimize a linear image reconstruction matrix R GREIT to desired performance measures by using learning strategy, which minimizes an error e 2 through a set of "training target". [6] where the sum k is over all training measurement and noise samples, σ (k) denotes the desired reconstructed image, ν (k) represents the boundary voltages of the "training target", w is the weight matrix which was defined to adjust the condition of the target.…”
Section: Inverse Problemmentioning
confidence: 99%
“…One widely used functional EIT parameter to classify the heterogeneity of lung ventilation is the "global inhomogeneity" (GI) index (6)(7)(8)(9)(10)(11)(12), proposed a decade ago by some of us. A recent survey suggested that the GI index is well-accepted and considered clinically useful (13).…”
Section: Introductionmentioning
confidence: 99%
“…20 Efecto de PEEP en el sistema respiratorio: el ajustar un nivel alto de PEEP tiene por objetivo mantener abiertos los alveolos previamente reclutados, abiertos, pero por otra parte, tomando en cuenta que el daño pulmonar es heterogéneo en el SDRA, los alveolos que presentan menor daño o intactos pueden generar daño por sobredistensión, 21,22 causado por la tensión secundaria a la presión positiva otorgada por el ventilador mecánico, contamos con distintas formas para evaluar esta característica; en la curva de presión-volumen se puede observar un «pico horizontal» cuando se llega al máximo de presión, que no es correspondido por un aumento proporcional del volumen, indicándonos que existe presión positiva sobre el alveolo, que no le genera ganancia de volumen, únicamente tensión; se han realizado estudios de tomografía por impedancia eléctrica para determinar cuál es la PEEP óptima para el paciente, en la cual se observan los alveolos colapsados, alveolos abiertos reclutados y alveolos sobredistendidos, lo cual puede ayudarnos a seleccionar un nivel de PEEP que genere la mayor apertura alveolar, con el menor grado de sobredistensión. 23,24 La sobredistensión alveolar generada por PEEP alta puede condicionar colapso de los vasos capilares adyacentes a las unidades alveolares, contribuyendo al aumento de las resistencias vasculares pulmonares y pudiendo generar hipertensión pulmonar inducida por el ventilador mecánico (Figura 3). La presión de distensión alveolar (DP, por sus siglas en inglés driving pressure) es la diferencia entre la presión meseta y la PEEP y representa la tensión cíclica a la que se somete el parénquima pulmonar durante cada ciclo ventilatorio, aumentar el nivel de PEEP puede disminuir la DP al aumentar la presión transpulmonar y mantener los alveolos reclutados, así como la disminución de la DP demuestra un aumento de la Cest del paciente.…”
Section: Efectos Sistémicos De La Peepunclassified